Pengembangan Ekowisata di Desa Nyambu Kecamatan Kediri Kabupaten Tabanan - LESMANA, CANDRA; SUAMBA, I KETUT; DJELANTIK, A.A.A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
Ecotourism Development in Nyambu Village, Kediri Sub-district, Tabanan Regency.  Nyambu Village is an agricultural area located at the southern tip of Tabanan Regency, Bali Province. The sustainability of the agricultural system in Bali is very dependent on the subak irrigation system. Subak Mundeh, which is located in Nyambu Village, is very suitable to be developed as an object of ecotourism. The development of agriculture-based ecotourism is a tourism development model that has the potential to develop the agricultural and tourism sectors. Many factors influence the success of an ecotourism, so it is important to know the role of the Nyambu Village community and Subak Mundeh farmers in the development of Nyambu Village Ecotourism. This study used a descriptive analysis method with a research instrument in the form of a questionnaire. The number of respondents was 70 people, who were selected by accidental sampling technique. This research shows that Subak Mundeh farmers and the people of Nyambu Village work together in developing Nyambu Village Ecotourism, namely by preserving traditional arts and culture, subak regulations, historical monuments, and maintaining the sustainability of the environment. The Government should provide more support so that the development of Nyambu Village Ecotourism could be better.